THE NEW ERA OF LIBERAL ARTS: TAILORING PRACTICAL EDUCATION FOR INTERNATIONAL ECONOMICS AND TRADE - Li, Chen Jia; Hong, Liu Xiao (Research Journal of Education and Allied Studies, 2024)
The field of international economy and trade is evolving in response to the accelerating forces of globalization and shifting economic landscapes. Traditional theoretical coursework is no longer sufficient to equip students with the practical skills and abilities demanded by these new challenges. Consequently, there is a growing focus on developing a practical teaching system for international economy and trade programs within higher education institutions. This paper delves into the international landscape, where scholars have proposed various theoretical frameworks and practical experiences. These offer valuable insights and inspiration for enhancing education in this field. For instance, Yulian J has explored talent cultivation models emphasizing practical teaching projects to nurture students' practical skills, teamwork, and innovative thinking. Wu G has examined strategies for adapting international economy and trade to the e-commerce environment, emphasizing collaboration among universities, enterprises, and government institutions. Shuo C has explored the integration of practical teaching in music education to enhance students' comprehensive skills and crossdisciplinary abilities. While these studies have made valuable contributions, challenges such as limited practical resources and the integration of practical and theoretical coursework persist. This article focuses on cultivating practical abilities, promoting interdisciplinary integration, fostering a seamless blend of theory and practice, introducing innovative teaching methods, and offering personalized learning support.